“Be Aware of Dogs!” in Context of Post-Folklore Linguistics - E. N. Ilyina (Научный диалог)
The problem of the analysis of polycode texts of mass communication, the functioning of which is determined by their collective authorship, as well as the active variation of their verbal and non-verbal components, while maintaining the plot-thematic, motive and character characteristics associated with specific genres of folk art, is considered. The relevance of such reflections is due to the fact that in the context of the development of Internet communications, the traditions of folk verbal creativity are gaining new life, including with the support of the technological capabilities of convergent media. The focus of this work is a corpus of texts that implement the motive of the ban on entering a certain territory. The analysis of polycode content in this article is carried out in the context of reflections on post-folklore as a special area of folk art of modern man, the distinctive properties of post-folklore texts and the practices of their linguistic analysis existing in modern science. It is shown that texts that have the characteristic properties of postmodernism culture (secondary, precedent, irony, game mode) and network culture (multimedia, intertextuality and interactivity) can be attributed to the field of network folklore and analyzed as Internet memes that continue the traditions of folk pictures, popular prints and other forms of creative polycode texts of non-author’s communication.